Hubungan antara Tingkat Spiritual dengan Tingkat Kecemasan pada Pasien Ca Mamae di Semarang - Siti Nur Rochmayanti; Wahyu Endang Setyowati; Dwi Heppy Rochmawati (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Anxiety is an emotional condition that causes feelings of discomfort, helplessness, and uncertainty, often without a clear reason. Among breast cancer (carcinoma mammae) patients, anxiety commonly arises due to treatment processes, physical changes, and uncertainty regarding recovery. Spirituality, which involves belief in God Almighty and connection with transcendental aspects, is believed to help individuals cope with uncertain and challenging situations, including serious illness. This study aimed to determine the relationship between spiritual level and anxiety level among breast cancer patients in Semarang. The research used a quantitative correlational design with a sample of 110 respondents selected through purposive sampling based on inclusion criteria. The instruments employed were the Depression Anxiety Stress Scale (DASS-42) to assess anxiety levels and the Daily Spiritual Experience Scale (DSES) to measure spirituality. Data were analyzed using the Chi-Square test to examine the relationship between variables. The results showed a p-value of 0.000 (p < 0.05), indicating a significant relationship between spirituality level and anxiety level in breast cancer patients. The findings suggest that higher levels of spirituality are associated with lower anxiety levels. Therefore, interventions that support and strengthen spiritual aspects may be effective in reducing anxiety among breast cancer patients. This study recommends that healthcare professionals incorporate spiritual approaches as part of holistic care to improve psychological well-being in patients undergoing cancer treatment.